L(a)ying with Marshall McLuhan: Media Theory as Hoax Art (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | This artist-response essay examines some ethical and aesthetic contours of media-theoretical hoaxes (and of a hoaxing media theory). I accomplish this through an exploratory reflection upon my own experiences and dilemmas as a media hoax artist, a vocation that has been influenced by Harold Adams Innis’s “authentic” scholarly persona as well as by McLuhan’s “probing” methods. Whereas recent work in the field of hoax art has tended to rely on the eventual text-bound revelation of the truth of the situation, my McLuhanite method aims rather towards magic and mediation.Résumé | Cet essai et réponse d’artiste examine quelques contours éthiques et esthétiques des canulars médiatiques (et d’une théorie des canulars médiatiques). J’accomplis cela à travers une réflexion exploratoire sur mes propres expériences et dilemmes en tant qu’artiste de canular médiatiques, une vocation qui a été influencée par la personnalité académique « authentique » d’Harold Adams Innis ainsi que par les méthodes « exploratoires » de McLuhan. Alors que les travaux récents dans le domaine de l’art du canular ont eu tendance à dépendre de la révélation éventuelle de la vérité de la situation, ma méthode McLuhanite s’appuie plutôt sur la magie et la médiation.